ANALISIS MODEL MATEMATIKA SEITR PADA PENYAKIT CACAR AIR - Musarifa; Hikmah; Fardinah (Program Studi Matematika Universitas Sulawesi Barat, 2021)
Chickenpox is an infectious disease caused by the varicella zoster virus. This infectious disease generally occurs not only in children but also attack adults and the nature of its transmission is so capidly. The purpose of this research is to build a model and analyze the SEITR (Susceptible-Exposed-Infected-Treatment-Recovered) mathematical model. The results obtained from the SEITR model have two equilibrium points, namely disease-free and endemic. Model analysis was performed using the Routh-Horwitz criteria to identify the eigenvalues. Based on the results of the stability analysis that the disease-free equilibrium point were stable if the condition for the relationship between parameters were met. At the end of the study,on the simulation that has been carried out it is found that this disease will when is 0,58 and this disease will be epidemic when is 2,80.